Just beat it: Exploring the influences of competition and task-related factors in gamified learning environments - Rodrigues, Luiz; Toda, Armando M.; Oliveira, Wilk; Palomino, Paula T.; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
Understanding how each game element in isolation affects learners' motivation and contextual factors' moderator effects is needed to improve gamified interventions. Thus, this paper explored the impact of one of the most used game elements - Competition - on motivation and whether task-related contextual factors (e.g., familiarity with the task's subject) moderate that impact. In a within-subject quasi-experimental design, graduate students from an Artificial Intelligence course created a reflexive intelligent agent for a console-based fight simulator in a non-gamified condition. Then, they improved their agents to compete against their peers agents (gamified condition). Based on motivation levels measured in both conditions, we found that Competition was positive for students and that task-related contextual factors influenced that effect. Therefore, suggesting i) Competition alone can be positive for motivation and ii) contextual moderators should be considered in defining gamified designs.